Physical activity, physical function and quality of life in community-based maintenance cardiac rehabilitation. (August 2019) - Hately, Garrick; Mandic, Sandra
Objective: This study compared physical activity (PA), physical function and quality of life in elderly individuals with coronary artery disease (CAD) and their non-CAD peers participating in community-based, maintenance cardiac rehabilitation (CR). Design: Cross-sectional study. Setting: Community-based maintenance CR programme. Methods: A total of 39 individuals (71.8% women; age 70.5 ± 5.5 years; 13 CAD, 26 non-CAD) wore an accelerometer for 7 days and completed anthropometry, chair stands, handgrip strength, a Short Physical Performance Battery, a PA questionnaire (IPAQ- SF), a quality of life questionnaire (SF-36), a 10-m shuttle walk test and two 6-minute walk tests. Results: Compared with the non-CAD group, the CAD group accumulated more objectively measured moderate-to-vigorous PA per week (329.7 ± 233.3 vs 160.6 ± 149.5 minutes, p  = .013), achieved PA guidelines on more days per week (3.8 ± 2.2 vs 2.1 ± 2.6 days/week, p  = .042), had a lower proportion of body fat (27.5 ± 8.4% vs 36.5 ± 8.7%, p  = .004) and a higher proportion of muscle mass (72.5 ± 8.4% vs 63.0 ± 9.8%, p  = .022). Physical function and quality of life were not different between the groups. Conclusion: Elderly CAD patients participating in community-based maintenance CR performed more PA and had more favourable body composition but similar physical function and quality of life compared with their non-CAD peers. Long-term participation in community-based maintenance CR may promote PA in elderly CAD patients and help maintain physical function and quality of life at a level similar to that of their non-CAD peers. However, due to a small sample size, these findings should be interpreted with caution and examined in future larger studies.